Designation and Control of Landing Points for Competitive Robotic Table Tennis. (15th July 2015) - Li, Jing; Chen, Xiaopeng; Huang, Qiang; Chen, Xuechao; Yu, Zhangguo; Duo, Yingxian
Competitive robotic table tennis involves many topics such as smart ball returning strategy, precise motion control, etc. It remains a quite challenging task due to the unpredictable, uncooperative incoming ball and the requirement of a smart strategy to defeat the opponent. Designation and control of landing points is one basic aspect of ball returning strategies in competitive robotic table tennis because different landing points require the opponent to make different efforts to return the ball. In this paper, we present a method to designate desired landing points based on competitiveness level. We also propose a learning based landing point control approach to minimize the error of the actual landing points with respect to the designated landing points. The proposed methods have been verified through experiments on a humanoid table tennis robot.